Bridging Employees’ Perceptions of Corporate Social Responsibility and Work Engagement through Organizational Commitment in an Indonesian Infrastructure Context - Oom Komalasari; Wiwi Hartati; Sylvani (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study investigates the extent to which employees’ perceptions of Corporate Social Responsibility (CSR) shape their level of work engagement, positioning organizational commitment as an intervening mechanism. The analysis draws on the case of PT Jasamarga Transjawa Tol in Indonesia. Grounded in the growing academic discourse on internal CSR implications, this research employs a quantitative methodology involving a saturated sample of 161 employees. It utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) for statistical evaluation. The findings reveal that employees’ perceptions of CSR have a positive and statistically significant effect on both organizational commitment and work engagement. Moreover, organizational commitment emerges as a key mediating construct that links CSR perception to employee engagement. These insights clarify the psychological mechanisms through which CSR initiatives impact employee attitudes, highlighting organizational commitment as a critical pathway to enhanced engagement. Ultimately, this study contributes to the literature on organizational behavior by presenting empirical evidence that reinforces the strategic relevance of internal CSR in fostering a committed and engaged workforce, particularly in the context of public infrastructure organizations.